2018
DOI: 10.1007/s00383-018-4301-x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of sonoelastography in predicting pediatric cervical lymph node malignancy

Abstract: Sonoelastography may be superior to other US modalities in elucidating different cervical lymph node biopsy helping to distinguish benign from malignant lesions. This may replace the lymph node biopsies in the future. Moreover, its use in the follow-up of patients with cervical malignancies may reduce the number of future biopsies. Further studies with more patients may be needed for a better assessment of results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…The study by Alam et al was similar to the study done by Zakaria et al [28]. Our study had tuberculosis and chronic granulomatous inflammation cases, which had given false-positive results as metastasis, leading to lower specificity and diagnostic accuracy.…”
Section: Discussionsupporting
confidence: 78%
“…The study by Alam et al was similar to the study done by Zakaria et al [28]. Our study had tuberculosis and chronic granulomatous inflammation cases, which had given false-positive results as metastasis, leading to lower specificity and diagnostic accuracy.…”
Section: Discussionsupporting
confidence: 78%
“…In selected cases, computed tomography or magnetic resonance imaging can be used to gain further information. Ultrasound elastography can also be used as an adjunct tool for sonographic findings, which can improve the accuracy of predicting malignant lymph nodes [ 2 ]. Thick cortex with loss of fatty hilum, central necrosis and a heterogeneous echo pattern with hyperechoic foci are suspicious characteristics in imaging modalities.…”
Section: Preoperative: Evaluation Images Special Needs and Biopsy Needmentioning
confidence: 99%
“…In 2018, a prospective study reported excellent results of elastography in predicting malignant cervical lymphadenopathy in children compared with tissue sampling. 14 Interestingly, they also declared that such tool may be an option in the future to replace surgical biopsies and to follow-up children with cervical malignancies. We agree with their findings regarding increased sensitivity and specificity of elastography when combined with other ultrasound modalities, whereas we do not agree with their conclusion about the future potential replacement of biopsies by elastography or by any radiological modalities.…”
Section: Discussionmentioning
confidence: 99%